The Generalized Theory of Transfers and Welfare: Bilateral Transfers in a Multilateral World - Bhagwati, Jagdish N.; Brecher, Richard A.; Hatta, Tatsuo (American Economic Review, 1983)
We demonstrate that the phenomenon of immiserizing transfers from abroad (and the analytically symmetric phenomenon of enriching transfer payments) in the presence of market stability can arise only if there is a distortion characterizing the economy in question.